The cGAS-STING pathway in atherosclerosis - Si-yu Wang; Si-yu Wang; Si-yu Wang; Yu-shan Chen; Yu-shan Chen; Bo-yuan Jin; Bo-yuan Jin; Bo-yuan Jin; Ahmad Bilal; Ahmad Bilal; Ahmad Bilal (Frontiers in Cardiovascular Medicine)
Atherosclerosis (AS), a chronic inflammatory disease, remains a leading contributor to cardiovascular morbidity and mortality. Recent studies highlight the critical role of the cGAS-STING pathway—a key innate immune signaling cascade—in driving AS progression. This pathway is activated by cytoplasmic DNA from damaged cells, thereby triggering inflammation and accelerating plaque formation. While risk factors such as aging, obesity, smoking, hypertension, and diabetes are known to exacerbate AS, emerging evidence suggests that these factors may also enhance cGAS-STING pathway, which amplifies inflammatory responses. Targeting this pathway offers a promising therapeutic strategy to reduce the burden of cardiovascular diseases (CVD). In this review, we summarize the mechanisms of the cGAS-STING pathway, explore its role in AS, and evaluate potential inhibitors as future therapeutic candidates. By integrating current knowledge, we aim to provide insights for developing novel treatments to mitigate AS and CVD burden.